How to Domesticate Otherness: Three Metaphors of Otherness in the European Cultural Tradition - Kroflic, Robi (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2007)
Individual and collective identities always develop in relation to the other as different, and in this process, the otherness is always subjected to the attempts of cultivation/domestication. In the history of European thought, we can recognize three metaphors which express the impossibility of seeing the other as different: the metaphors of The Leper, The Court Fool and The Noble Savage. They developed on the basis of the relationship between the difference and common rationality, which means that a more inclusive relationship to otherness as a conversational ideal could be formed if we were able shift the emphasis of ethical discourse from the universal concept of autonomy to respect for authenticity and to Levinas’s ethics of “the face of the other”. Such a step requires a radical change of discursive practices of all involved in the educational processes. That is why I propose the principle of observing the face of the other as different in both real-life experience and in expressive images of art, as well as the recognition and acceptance of otherness at the very core of our own identity.